An Examination of Collective Memory of the Tsunami Disaster: A Comparative Study between Japan and Indonesia - Murti, Desideria Cempaka Wijaya; Marta, Rustono Farady; Almuntarizi, Almuntarizi; Manalu, Tifani Dianisya (JURNAL KOMUNIKASI INDONESIA, 2023)
Japan and Indonesia, as two countries that are geographically vulnerable to tsunami disasters, have similarities in geography and culture. Analyzing disaster museums through the Inamura No Hi Museum in Japan and the Aceh Museum in Indonesia in communication, heritage, and cultural studies were conducted to show how museums' visual framework and experience are used to interpret post-disaster situations. This study aims to see how the Japanese and Indonesian disaster museums, closely related to visuals and local legends, convey information to educate the public about mitigation through the memory of the Tsunami disaster in the museum. This research is a comparative qualitative study with native ethnography as the method. This study analyzes three important theoretical aspects in establishing disaster memory through museums, and those are: information processing theory, disaster memory, and visual performing theory. In this study, there are three findings where the memory of the disaster is manifested in the Aceh museum and Inamura no hino Yakata: buildings, exhibitions, and audio-visual media.